The Impact of Plate Length and Material Variations on Tibial Bone Implants Analysis using Computational Biomechanics - Sakinah, Sakinah; Wardhani, Primasari Cahya; Rizkiarna, Reffany Choiru; Aminallah, Deliana Nurfauziyyah; Aruan, Nenni Mona; Billah, Zakiyah Dania (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
The aim of this research is to simulate the strength of the implant plate, as a method for healing tibia fractures by combining bone with a bone plate. Then model and analyze using ANSYS software to analyze loads such as deformation and the maximum distribution of von Mises stress values. The results of the Maximum Principal Stress analysis on the cobalt-chromium implant plate show a minimum value of -1.2527107 Pa (-12.527 MPa) and a maximum value of 7.57610 7Pa (75.76 MPa). Based on the research results, Co-Cr material has significant advantages compared to steel as an implant material. In addition, this material has excellent corrosion resistance and very good biocompatibility, making it safe for long-term use in the human body without significant risk of allergic reactions or irritation.